The Current State of Fiscal Transparency : Norms, Assessment, and Country Practices - Petrie, Murray (World Bank, Washington, DC, 2018)
Over the last 15 years, there has been a growing effort globally to promote fiscal transparency, reflecting both that the public has a right to information, and that transparency contributes to more equitable, efficient, and effective fiscal policies. However, the overall state of budget transparency is poor: measured against the Open Budget Index, the national budgets of 77 countries, home to half the world’s population, fail to meet basic standards of budget transparency. Efforts are underway to improve the coherence of the multiplicity of standards, strengthen the assessment of country practices, and to address important gaps in the normative architecture, such as norms for legislative oversight and direct public participation. Many governments could rapidly improve transparency by publishing reports they already produce internally, which points to the need to strengthen incentives for governments to be more transparent.